Validação de jogos didáticos utilizados para o ensino de Química - Carvalho, Francimary Cabral (2018)
The Periodic Table is a complex theme for many students due to the difficulty of understanding their concepts, making it essential to provide educational tools that contribute to the assimilation of content. This study was developed considering the bibliographic survey, game selection, validation, game application, verification of learning and the elaboration of a didactic resource kit. This work has a qualitative approach, having as a methodological strategy the Research-Action. The research was developed with students and professors of the Federal Institute of Education, Science and Technology of Amazonas - IFAM. The selection of the games was done through consultation with the IFAM library records, consultation of the electronic records of the Academic Department of Basic Education and Teacher Training (DAEF) of the chemistry degree course, referring to PIBID projects from 2010 to 2014 and PRODOCENCE from 2008 to 2010. The Enigma Periodic and Chemical Profile games were selected, which were submitted to a content validation. The validation was carried out through the application of the games and subsequent evaluation of their attributes by the 7th period chemistry graduates and effective professors of the degree in chemistry, where through their specific knowledge about chemistry, methodology and didactics they critically analyzed the material proposed as a playful resource for the teaching of Periodic Table. Through the analysis of the information of the applied questionnaires, a content concordance analysis was generated among the evaluators regarding the formative aspects of the learning of the games, level of the content addressed by the games and playfulness. The games were reviewed, reprinted and applied in the 1st year of high school to measure how much the games influenced the learning process. The results obtained were excellent, with learning yield of approximately 78%, after the application of the periodic Enigma game and 71% after the application of the game Chemical profile. Before the application of the games the yield was 46%. In this context, it was evident the improvement of the use of the class, which justifies the effectiveness of play games validated in the present work. The Enigma Periodic and Chemical Profile games are promising tools to aid in the understanding of contents related to the Periodic Classification of Elements, and can be constructed with materials of low cost, which makes it a didactic material accessible to all.